A deep insight into the toxic mechanism for sulfonamides based on bacterial cell-cell communication. (August 2019) - Sun, Haoyu; Yao, Zhifeng; Wang, Dali; Wu, Xiaodan; Lin, Zhifen; Liu, Ying
Abstract: Sulfonamides (SAs), a kind of commonly used antibiotics, have been frequently detected in the environment. Due to their potential threat to the ecological environment, the toxicity of SAs to bacteria have been determined in depth, and the toxic mechanism is found to target dihydropteroate synthase (DHPS). However, other toxic mechanism may also exist for SAs, which is still unclear to us. In this paper, the toxic mechanism of sulfachloropyridazine (SCP, as a representative of SAs) was investigated thoroughly on Aliivibrio fischeri ( A. fischeri ) from the perspective of quorum sensing (QS). The results reveal that SCP may act on three signaling pathways, i.e., Pathway I, II and III, which triggers, maintains and destroys the homeostasis of A. fischeri respectively. In Pathway I, SCP changes the active form of LitR that regulates the expression of lux -related genes, inducing inhibition on bacterial growth while stimulation on luminescence; in Pathway II, SCP facilitates the production of C6HSL signaling molecules, maintaining the homeostasis in LitR and DHPS proteins; whereas in Pathway III, SCP typically combines with DHPS to inhibit the folate metabolism. This study can provide a deeper and more comprehensive understanding on the toxicity of SAs and help the environmental risk assessment of SAs. Graphical abstract: Unlabelled Image Highlights: SCP may act on three signaling pathways (Pathway I, II, and III) in A. fischeri . SCP changes the active form of LitR to trigger the homeostasis in Pathway I. SCP facilitates the C6HSL signals to maintain the homeostasis in Pathway II. SCP combines with DHPS to destroy the homeostasis in Pathway III.